2010
DOI: 10.1371/journal.pone.0012501
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aging on the Molecular and Cellular Composition of the Prostate Microenvironment

Abstract: BackgroundAdvancing age is associated with substantial increases in the incidence rates of common diseases affecting the prostate gland including benign prostatic hyperplasia (BPH) and prostate carcinoma. The prostate is comprised of a functional secretory epithelium, a basal epithelium, and a supporting stroma comprised of structural elements, and a spectrum of cell types that includes smooth muscle cells, fibroblasts, and inflammatory cells. As reciprocal interactions between epithelium and stromal constitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
85
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 72 publications
12
85
0
6
Order By: Relevance
“…Moreover, a recent in vivo wound healing study linked mechanical forces to inflammatory activation of fibroblasts via focal adhesion kinase (FAK), a transducer of both inflammatory and physical signals: In a mouse model of hypertrophic scar formation, fibroblast-specific knockdown of FAK resulted in reduced inflammation and fibrosis, compared with control mice [50]. While not involving cancer, these studies indicate that changes in tissue architecture as a result of aberrant epithelial proliferation, an early neoplastic response, may result in activation of inflammatory signalling by stromal fibroblasts, a hypothesis supported by reports of inflammatory signalling by stromal fibroblasts in benign prostatic hyperplasia [50][51][52][53]. Taken together, it is reasonable to hypothesize that biomechanical forces applied by aberrant proliferation of transformed epithelial cells in incipient tumours may be one of the physiological signals that trigger pro-inflammatory signalling in resident tissue fibroblasts.…”
Section: Activation By Biomechanical Forcesmentioning
confidence: 74%
“…Moreover, a recent in vivo wound healing study linked mechanical forces to inflammatory activation of fibroblasts via focal adhesion kinase (FAK), a transducer of both inflammatory and physical signals: In a mouse model of hypertrophic scar formation, fibroblast-specific knockdown of FAK resulted in reduced inflammation and fibrosis, compared with control mice [50]. While not involving cancer, these studies indicate that changes in tissue architecture as a result of aberrant epithelial proliferation, an early neoplastic response, may result in activation of inflammatory signalling by stromal fibroblasts, a hypothesis supported by reports of inflammatory signalling by stromal fibroblasts in benign prostatic hyperplasia [50][51][52][53]. Taken together, it is reasonable to hypothesize that biomechanical forces applied by aberrant proliferation of transformed epithelial cells in incipient tumours may be one of the physiological signals that trigger pro-inflammatory signalling in resident tissue fibroblasts.…”
Section: Activation By Biomechanical Forcesmentioning
confidence: 74%
“…It is caused by an imbalance between the production of reactive oxygen species (ROS) and their detoxification by enzymes, such as catalase and manganese superoxide dismutase (MnSOD). OS related to age, 15 inflammation and nutrition, 16 as well as exposure to androgens, 17 leads to pro-carcinogenic events, in particular accumulation of oxidative DNA damage. Likewise, it has been suggested that compared with normal subjects or patients with BPH, PC patients have a systemic imbalance in their OS/anti-oxidant status.…”
Section: Introductionmentioning
confidence: 99%
“…Bianchi-Frias et al quantified transcription levels in microdissected glandular-adjacent stroma from young (age 4 months) and old (age 20 -24 months) C57BL/6 mice, and identified macrophages, as well as inflammation-associated genes CCL8, CCL12, CCL5, and CCL7, were significantly increased in the aged prostatic stroma (45), suggesting that macrophages could play an important role in promoting chemokine induction and prostatic stroma expansion.…”
Section: Discussionmentioning
confidence: 99%